Unjuk Kerja Termal Kolektor Surya PV/T Bersirip Menggunakan Metode Computing Fluid Dynamic - Nalis, Amrizal; Irsyad, Muhammad; Yonanda, Ahmad; Khairudin, Rizal (P3M Politeknik Negeri Cilacap, 2023)
Photovoltaic Thermal (PV/T) collector is a device that can produce electrical energy and thermal energy simultaneously. However, the thermal energy increases the surface temperature of the PV and therefore it may reduce electrical efficiency. To overcome this problem, a finned thermal collector should be joined underneath the PV surface. The aim of this study is to simulate the thermal performance of a PV/T collector by using staggered fins with air as a working fluid. The parameters are varied from 25 to 50 mm in the fin geometry and from 12 to 48 g/s in air mass flow rate, respectively. Furthermore, the heat radiation used was 860 Wâ„m2 and Computing Fluid Dynamic (CFD) method was implemented in this research. The results showed that the PV/T surface temperature decreased by 7.04 % for the fin height of 37.5 mm and 11.9 % for the fin height of 50 mm when compared to the fin height of 25 mm. Thus, a greater cooling of the PV/T surface occurs in the fin height of 50 mm due to an increase in the heat transfer area which might absorb more of the unused thermal energy in comparison with others.